Algoritma K-Means Untuk Mengetahui Minat Siswa Terhadap Jurusan Teknik Informatika - putri dina mardika (LPPM, 2023)
There are already many information technology-based companies in the capital city, many job vacancies may be opened because they require experts with an educational background in informatics engineering. The research was conducted on YMIK 2 Jakarta high school students who concentrated on science and social studies. YMIK 2 High School students are familiar with information technology devices because there is a computer lab as a student facility for conducting computer learning activities. And there is an internet network in the form of free wifi at school. Researchers used data mining techniques with the K-Means algorithm and RapidMiner tools to process data to produce some conclusions about groupings related to whether or not YMIK 2 Jakarta High School students are interested in the Informatics Engineering major. The researcher divided the clusters into 2 groups consisting of cluster_0 which means students who are interested in informatics engineering and cluster_1 which means students who are not interested in informatics engineering. The data set used in this study was 50 data, according to the students participating in SMA YMIK 2 Jakarta. From the results of this study, it is known that students who are interested in majoring in informatics engineering are more numerous than students who are not interested in majoring in informatics engineering based on the k-means clustering algorithm.